ANALISIS PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN PADA PT. ENSEVAL PUTERA MEGATRADING, TBK CABANG PANGKALPINANG - Yori; Novika; Panjaitan, Fery (STIE IBEK Pangkalpinang, 2023)
This study uses primary data with quantitative descriptive. The data used in this study is in the form of questionnaires to 52 employees. The sampling technique is the same as the total population at PT. Enseval Putera Megatrading, Tbk Pangkalpinang Branch. The data analysis method used is descriptive statistics with hypothesis testing using multiple linear regression processed with JASP. The results of the study show (1) Control Environment has no partial effect on employee performance with a significance value of 0.813. (2) Risk assessment has no partial effect on employee performance with a significance value of 0.239. (3) Control activities have no partial effect on employee performance with a significance value of 0.230. (4) Information and Communication has no partial effect on employee performance with a significance value of 0.968. (5) Monitoring has a partial effect on employee performance with a significance value of 0.020. (6) Control Environment, Risk Assessment, Control Activities, Information and Communication and Monitoring have a simultaneous effect with a significance value of 0.001.